Effect of Transfusion on the Extension of IVH in Preterm Neonates - Ali Reza Jashni Motlagh; Azamolmolouk Elsagh (Mashhad University of Medical Sciences, 2020)
Background: Today, preterm birth is well known as the major risk factor for intraventricular hemorrhage (IVH). In the first week of life, some preterm infants may have grade 1 IVH extending to severe (grade 3 or 4) IVH by transfusion one or more units. Several previous studies have found that blood and blood product transfusions lead to adverse clinical outcomes in neonates. Therefore, this study aimed to explore the relationship between Red blood cell (RBC) transfusion and extension of IVH in preterm infants. Methods: For the purposes of the study, an observational retrospective case-control design was utilized. Moreover, all the neonates with grade 1 IVH in our referral hospital were identified in the past 5 years. Afterward, the subjects with extended IVH were compared with those who had resolved IVH. Results: In total, 1050, 36, and 24 neonates were diagnosed with grade 1, grade 3, and grade 4 IVH, respectively. The mean values of the birth weight of extended IVH and resolved IVH groups were 1285±615 g and 1361±348 g, respectively (P=0.05). Moreover, extended IVH and resolved IVH groups were 29±3 weeks and 30±2 weeks premature, respectively (P=0.36). The low 5-minute Apgar scores of the extended IVH and resolved IVH groups were 5±2 and 7±2, respectively (P=0.000). In addition, the low cord pH of the extended IVH and resolved IVH groups were 7.29±0.1 and 7.37±0.1, respectively (P=0.005). Administration of packed RBC transfusion before and on the day of the diagnosis of grade 1 IVH had the most significant relationship with the extension of IVH (IR, 10.602; 95% CI, 2.81-39.92). The obtained results confirmed that criteria to order the transfusions were similar in both groups, based on which they did not have any proportion of the transfusions of compliance with the guidelines. Conclusion: Based on the results, there was a great association between restrictive RBC transfusion and extension of a low-grade IVH into a higher grade (3 or 4) IVH. However, the statistical explanation is unclear and more studies are needed to discover the causality of this relationship.